Manusia, Lingkungan, dan Kebudayaan: Kajian Tentang Teori Adaptasi Manusia dan Lingkungan - La Malihu (Rayhan Intermedia, 2023)
The view that culture is a system of human conditions and the environment has long been developed. But until now there is no single theory that can be used as the main key to analyze various cultural realities that occur in various places. This article tries to analyze the theories that have developed related to the view that culture is a system of human adaptation to the environment. The method used is a literature review to identify, evaluate, and systematically the theories put forward by experts. The results of the study show that because of the complexity of human life, so far there is no single approach that can absolutely become an